Case Study of Inventory Management for Biology Laboratory Materials using ERP System - Teddy Marcus Zakaria; Wahyu Widowati; Bernard Renaldy Suteja (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2023)
Efficient inventory management is essential for biology laboratories to ensure the availability of materials for research and experiments. This case study explores the implementation of an Enterprise Resource Planning (ERP) system for inventory management in a biology laboratory. The objective is to enhance inventory control, streamline processes, and improve overall efficiency. The ERP system was implemented to address inventory management challenges and improve the accuracy and transparency of material tracking. The study assessed the impact of the ERP system on inventory control, procurement processes, and decision-making related to material planning. The findings of the case study demonstrate the benefits of implementing an ERP system for inventory management in a biology laboratory. The system provided real-time visibility of stock levels, enabling efficient tracking and monitoring of laboratory materials. It also automated procurement processes, reducing manual errors and streamlining the procurement cycle. The ERP system facilitated informed decision-making through data analytics, aiding in material planning and resource allocation. The successful implementation of the ERP system in the biology laboratory serves as a model for other similar laboratories seeking to enhance their inventory management practices. The case study emphasizes the significance of leveraging technology, such as ERP systems, to optimize inventory control and improve operational efficiency. The benefits include improved accuracy, reduced wastage, and increased productivity. This case study contributes to the existing knowledge on inventory management for biology laboratory materials and provides practical insights for organizations considering the implementation of an ERP system.